(untitled) (Revista de Biología Marina y Oceanografía, 2021)
Harvest pressure on brown macroalgae of the Lessonia genus has increased in recent years in Peru and Chile, due to the high demand from the global hydrocolloid industry. After a taxonomic review, in 2012, the intertidal species Lessonia nigrescens was segregated into two species, being L. berteroana distributed in southern Peru and northern Chile (17-30°S). Based on genetic tools we confirm the identification as L. berteroana and report its presence up to 15°23’S. It is recommended to update the status of the species into Peruvian regulations and scientific publications.